Effects of a strategy to improve offender assessment practices: Staff perceptions of implementation outcomes. (1st July 2015) - Welsh, Wayne N.; Lin, Hsiu-Ju; Peters, Roger H.; Stahler, Gerald J.; Lehman, Wayne E.K.; Stein, Lynda A.R.; Monico, Laura; Eggers, Michele; Abdel-Salam, Sami; Pierce, Joshua C.; Hunt, Elizabeth; Gallagher, Colleen; et al.
Highlights: An intervention to improve assessment for drug-involved offenders was tested. Outcomes included Measurement/Instrumentation and Case Plan Integration . Evidence-based assessment practices in correctional systems were improved. Stronger effects were obtained for intra- than inter-agency outcomes. Abstract: Background: This implementation study examined the impact of an organizational process improvement intervention (OPII) on a continuum of evidence based practices related to assessment and community reentry of drug-involved offenders: Measurement/Instrumentation, Case Plan Integration, Conveyance/Utility, and Service Activation/Delivery. Methods: To assess implementation outcomes (staff perceptions of evidence-based assessment practices), a survey was administered to correctional and treatment staff ( n = 1509) at 21 sites randomly assigned to an Early- or Delayed-Start condition. Hierarchical linear models with repeated measures were used to examine changes in evidence-based assessment practices over time, and organizational characteristics were examined as covariates to control for differences across the 21 research sites. Results: Results demonstrated significant intervention and sustainability effects for three of the four assessment domains examined, although stronger effects were obtained for intra- than inter-agency outcomes. No significant effects were found for Conveyance/Utility. Conclusions: Implementation interventions such as the OPII represent an important tool to enhance the use of evidence-based assessment practices in large and diverse correctional systems. Intra-agency assessment activities that were more directly under the control of correctional agencies were implemented most effectively. Activities in domains that required cross-systems collaboration were not as successfully implemented, although longer follow-up periods might afford detection of stronger effects.